Serum Elafin as a Potential Marker of Disease Activity in Behçet's Disease - Armagan Kutlay; Afet Akdag Kose (Wolters Kluwer Medknow Publications, 2023)
Background: Elafin is a serine protease inhibitor with anti-inflammatory properties. It is expressed in various epithelial tissues with increased production under inflammatory conditions. Increased tissue elafin expression in Behçet's disease (BD) lesions has previously been demonstrated. Aims and Objectives: We hypothesised that serum elafin might be increased in patients with BD and aimed to assess the relationship of serum elafin with disease activity and organ involvement in BD. Materials and Methods: Fifty-four BD patients (29 active, 25 inactive) and 30 healthy controls were included in this single-centre case-control study. Serum elafin was measured using ELISA. Complete blood count, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) tests were also performed. Results: Serum elafin levels were significantly higher in patients with BD (1.58 ± 0.47 ng/ml, range: 0.67-2.96) compared to controls (1.10 ± 0.28 ng/ml, range: 0.65-1.49) (P < 0.001). Patients with active BD had higher elafin levels than patients with inactive BD (P = 0.008). Active arthritis was associated with an increase in elafin (P = 0.012), while the presence of mucocutaneous symptoms was not. Serum elafin correlated significantly with ESR (P = 0.001). The ideal cut-off value for the diagnosis of BD was determined as 1.24 ng/ml with a sensitivity and specificity of 72.2% and 70.0%, respectively. Conclusion: Serum elafin is significantly increased in patients with BD. It may serve as a marker of disease activity, especially articular involvement.